Preparation of Progressive Driving Bilayer Polymer-Dispersed Liquid Crystals Possessing a PDLC-PVA-PDLC Structure - Yongle Wu; Yuzhen Zhao; Dong Wang (Molecules, 2024)
In this paper, the bilayer polymer-dispersed liquid crystals possessing a PDLC-PVA-PDLC structure were prepared by integrating two monolayer PDLCs. The effect of the polymer mesh size on the electro–optical properties of a bilayer PDLC was investigated by comparing the micro-morphology and electro–optical curves under different polymerization conditions. In addition, the impact of doping MoO2 nanoparticles with surface modification on the comprehensive performance of the bilayer PDLC was further researched. The contrast ratio of the bilayer PDLC prepared under the optimal conditions was improved by more than 90% and still maintained excellent progressive driving performance. Therefore, the development of a bilayer PDLC with optimal electro-optical properties will significantly enhance the technological prospects for the application of PDLC-based devices in smart windows, displays, and flexible devices.